Enchelycore propinqua sp. nov., a new moray eel (Anguilliformes: Muraenidae: Muraeninae) from the Indian Coast - Mohapatra, Anil; Smith, David G.; Mohanty, Swarup Ranjan; Mishra, Subhrendu Sekhar; Tudu, Prasad C. (Zootaxa, 2017)
A new moray Enchelycore propinqua sp. nov., is described from a single specimen collected from Visakhapatnam fishing harbour, Andhra Pradesh, India. The species has a reddish brown body mottled with irregular creamy white spots; dorsal-fin origin considerably behind gill opening, but well ahead of level of anus; sharply pointed recurved teeth; biserial intermaxillary and maxillary teeth, those of inner row larger and more widely spaced than outer row. It differs from congeners by higher predorsal vertebrae and lower total vertebral count (MVF 20-51-120). The colouration is distinctly different from other species of the genus.